Transcriptomic and Metabolomic Analyses of Diaphorina citri Kuwayama Infected and Non-infected With Candidatus Liberibacter Asiaticus - Liu, Kai; He, Jiawei; Guan, Ziying; Zhong, Mingzhao; Pang, Rui; Han, Qunxin (Frontiers in Physiology, 2021)
The Asian citrus psyllid Diaphorina citri is the transmission vector of Huanglongbing (HLB), a devastating disease of citrus plants. The bacterium ‘Candidatus Liberibacter asiaticus’ (CLas) associated with HLB is transmitted between host plants by D. citri in a circulative manner. Understanding the interaction between CLas and its insect vector is key for protecting citrus cultivation from HLB damage. Here, we used RNA sequencing and liquid chromatography-mass spectrometry (LC-MS) to analyze the transcriptome and metabolome of D. citri interacting with CLas. We identified 662 upregulated and 532 downregulated genes in CLas-infected insects. These genes were enriched in pathways involving carbohydrate metabolism, the insects’ immune system, and metabolism of cofactors and vitamins. We also detected 105 differential metabolites between CLas-infected and noninfected insects, including multiple nucleosides and lipid-related molecules. The integrated analysis revealed nine pathways—including those of the glycine, serine, threonine, and purine metabolism—affected by the differentially expressed genes from both groups. The network for these pathways was subsequently constructed. Our results thus provide insights regarding the cross-talk between the transcriptomic and metabolomic changes in D. citri in response to CLas infection, as well as information on the pathways and genes/metabolites related to the CLas–D. citri interaction.